RECOVERY OF POLY(3-HYDROXYBUTYRATE) FROM Yangia sp. ND199 BY SIMPLE DIGESTION WITH SODIUM HYPOCHLORITE - Doan, Thuoc Van; Hoi, Luu Thi; Phong, Tran Huu (Vietnam Journal of Science and Technology, 2015)
Polyhydroxyalkanoate (PHA) is a biodegradable polymer synthesized intracellularly by many microorganisms. After extraction from the cells, they possess the common features of non-toxic, biocompatible, biodegradable and recyclable. These features render them highly competitive with polypropylene or other petroleum-derived plastics, especially in medicine. The isolation and purification of PHA from bacterial cells are the key step of PHA production process. There are several methods have been used for OHA purification, these include solvent extraction, enzymatic hydrolysis, and chemical digestion. In this study we used chemical digestion method for purification of PHB from Yangia sp. ND199. Among various chemical tested (NaOH, HCl, KOH, NaOCl, and SDS), NaOCl was found as an efficient chemical for PHB recovery and PHB purity from Yangia sp. ND199. The optimal purity and recovery conditions were a ratio of 1:1 (v/v, solution containing 100 g/l bacterial cells and solution containing 6% NaOCl), a 30 oC temperature and a 1 h treatment time. Under such conditions, a purity of 99% and a recovery of 94% were obtained. This method is sumple and can be developed and used for industrial scale.